Labour Relations Practices of Nonprofits Acting as For-Profits: An Explainable Dissonance - Kimel, Eyal (Just Labour, 2006)
This article seeks to connect two seemingly distinct phenomena. Labour disputes in the nonprofit sector and the pressure nonprofits have undergone to become more economically and operationally efficient. The article describes the antics of some nonprofits in Ontario, and equates them with similar tactics that are employed by mega corporations that are notorious for their mistreatment of employees. The article endeavors to find a correlation between the mistreatment of employees by nonprofits and the ever-growing pressure, nonprofits have had to endure in recent years, to become more efficient. The author argues that the ethics of efficiency and corporate-like models of operation bring along other characteristics of for-profit businesses that may explain actions taken by nonprofits that are otherwise in direct contrast with everything they stand for.